Adaptasi Jurnalis Pikiran Rakyat Media Network Bandung di Era Kecerdasan Buatan - Azkia Nur Sa’diyyah; Heri Hendrawan; Feri Purnama (Lembaga Teewan Journal Solutions, 2026)
The rapid advancement of artificial intelligence (AI) has transformed the media industry and encouraged journalists to adapt to new forms of digital collaboration. This study aims to analyze how journalists at Pikiran Rakyat Media Network Bandung (PRMN) adapt to AI in their journalistic practices, identify factors influencing its adoption, and examine strategies for maintaining journalistic credibility. This research employed a qualitative descriptive approach using data triangulation through in-depth interviews, non-participant observation, document analysis, and expert informant interviews. Data were analyzed using the Miles and Huberman model and interpreted through Rogers' Diffusion of Innovation Theory. The findings show that PRMN integrates AI into three stages of the journalistic workflow: News Collecting, News Processing, and News Publishing. AI adoption has increased productivity, accelerated content production, and expanded analytical perspectives while remaining under human editorial control. The adoption process is driven by perceived benefits, institutional support, and search engine optimization (SEO) demands. To mitigate risks, PRMN implements evaluation forums, double verification procedures, AI-content labeling, and strict adherence to journalistic ethics. The study concludes that AI serves as a supporting tool that enhances journalists' capabilities rather than replacing their professional roles, highlighting the importance of adaptive capacity in successful AI adoption.